Weak correlation between antibody titers and neutralizing activity in sera from SARS‐CoV‐2 infected subjects - Criscuolo, Elena; Diotti, Roberta A.; Strollo, Marta; Rolla, Serena; Ambrosi, Alessandro; Locatelli, Massimo; Burioni, Roberto; Mancini, Nicasio; Clementi, Massimo; Clementi, Nicola (Journal of medical virology, 2021)
Plenty of serologic tests for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) have been developed so far, thus documenting the importance of evaluating the relevant features of the immune response to this viral agent. The performance of these assays is currently under investigation. Amongst them, LIAISON® SARS‐CoV‐2 S1/S2 IgG by DiaSorin and Elecsys Anti‐SARS‐CoV‐2 cobas® by Roche are currently used by laboratory medicine hospital departments in Italy and many other countries. In the present study, we firstly compared two serologic tests on serum samples collected at two different time points from 46 laboratory‐confirmed coronavirus disease‐2019 (COVID‐19) subjects. Secondly, 85 negative serum samples collected before the SARS‐CoV‐2 pandemic were analyzed. Thirdly, possible correlations between antibody levels and the resulting neutralizing activity against a clinical isolate of SARS‐CoV‐2 were evaluated. Results revealed that both tests are endowed with low sensitivity on the day of hospital admission, which increased to 97.8% and 100% for samples collected after 15 days for DiaSorin and Roche tests, respectively. The specificity evaluated for the two tests ranges from 96.5% to 100%, respectively. Importantly, a poor direct correlation between antibody titers and neutralizing activity levels was evidenced in the present study. These data further shed light on both potentials and possible limitations related to SARS‐CoV‐2 serology. In this context, great efforts are still necessary for investigating antibody kinetics to develop novel diagnostic algorithms. Moreover, further investigations on the role of neutralizing antibodies and their correlate of protection will be of paramount importance for the development of effective vaccines. Highlights A comparative analysis between two serologic assays for the detection of antibodies directed against SARS‐CoV‐2 was carried out on sera from subjects testing positive for SARS‐CoV‐2 nasopharyngeal swabs. Results revealed that both tests are endowed with low sensitivity on the day of hospital admission, which increased for samples collected after 15 days. A poor direct correlation between antibody titers and neutralizing activity levels was evidenced in the present study.